Advancing Justice and Democracy 'beyond' the State: Feasibility through Flexibility. (June 2016) - Kuyper, Jonathan W.
The literature on international political theory is replete with proposals to make world politics a more just and democratic place. This article explores how the cosmopolitan design project can be made more tractable in a world composed of sovereign nation states. Specifically, it argues that flexibility mechanisms – tools common in international cooperation – enhance the feasibility of design. The article draws upon the recent work on political feasibility and argues that economic, institutional and cultural constraints can be overcome by using flexibility mechanisms. In order to gain traction on the argument, prescriptions made in the field of intellectual property rights are analysed. Thomas Pogge and Allen Buchanan, Tony Cole and Robert Keohane have separately advanced institutional proposals to reform the global essential medicine system. The article details how feasibility can be enhanced through flexibility in light of these proposals, and makes a suggestion about their comparative feasibility and desirability.